Comparative analysis of energy homeostasis regulation at different altitudes in Hengduan Mountain of red-backed vole, Eothenomys miletus, during high-fat diet acclimation: examining gut microbial and physiological interactions - Jia, Ting; Zhang, Wei; Cao, Lijuan; Zhu, Wanlong; Fan, Lixian (Frontiers in Microbiology, 2024)
The study aimed to explore the similarities and differences in gut microorganisms and their functions in regulating body mass in Eothenomys miletus across different altitudes in the Hengduan Mountains when exposed to a high-fat diet. E. miletus specimens were gathered from Dali (DL) and Xianggelila (XGLL) in Yunnan Province, China, and categorized into control, high-fat (one week of high-fat diet), and re-feeding groups (one week of high-fat diet followed by two weeks of standard food). The analysis utilized 16S rRNA sequencing to assess the diversity and structure of intestinal microbial communities in E. miletus. The investigation focused on the impact of high-fat diet consumption and different altitudes on gut microbial diversity, structure, and physiological markers. Results revealed that a high-fat diet influenced the beta diversity of gut microorganisms in E. miletus, leading to variations in microbial community structure between the two regions with different altitudes. Highfat food significantly affected body mass, white adipose tissue mass, triglycerides, and leptin levels, but not food intake. Specific intestinal microorganisms were observed in the high-fat groups, aiding in food digestion and being enriched in particular flora. Notably, microbial genera like Lactobacillus and Hylemonella were enriched in the high-fat group of DL. The enriched microbiota in the control group was associated with plant polysaccharide and cellulose decomposition. Following a high-fat diet, gut microbiota adapted to support lipid metabolism and energy supply, while upon re-feeding, the focus shifted back to cellulose digestion. These findings suggested that alterations in gut microbial composition, alongside physiological markers, play a vital role in E. miletus' adaptation to the diverse habitats of the Hengduan Mountains at varying altitudes.